Modulating the Electron Transporting Properties of Subphthalocyanines for Inverted Perovskite Solar Cells - Labella, Jorge; Momblona, Cristina; Čulík, Pavel; López-Serrano, Elisa; Kanda, Hiroyuki; Nazeeruddin, Mohammad Khaja; Torres, Tomás (Frontiers in Chemistry, 2022)
The lack of organic non-fullerene ETMs with good electron transport and device stability is an important problem for the further development and commercialization of perovskite solar cells (PSCs). Herein, the use of SubPcs as ETMs in PSCs is explored. To this end, we analyze the influence of SubPc peripheral functionalization in the efficiency and stability of p-i-n PSCs. Specifically, ETMs based on three SubPcs (with either six or twelve peripheral fluorine and chlorine atoms) have been incorporated in PSCs with the perovskite layer deposited by solution processing (CsFAMAPbIBr). The device performance and morphology of these devices are deeply analyzed using several techniques, and the interfacial effects induced by the SubPcs are studied using PL and TR-PL. It is observed that the device stability is significantly improved upon insertion the SubPc layer. Moreover, the impact of SubPc layer-thickness is assessed. Thus, a maximum PCE of 13.6 % was achieved with the champion device.